Internal Migration, Regional Labour Market Dynamics and Implications for German East-West Disparities – Results from a Panel VAR - Björn Alecke; Timo Mitze; Gerhard Untiedt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper analyses the causal linkages between regional labour market variables and internal migration flows among German states between 1991-2006. We adopt a Panel VAR approach to identify the feedback effects among the variables and analyse the dynamic properties of the system through impulse-response functions. We also use the model to track the evolution of the particular East-West migration since re-unification aiming to shed more light on the East German empirical puzzle, characterized by lower migration responses than expected from the regional labour market position relative to the West. We indeed get evidence for such a puzzle throughout the mid-1990s, which is likely to be caused by huge West-East income transfers, a fast exogenously driven wage convergence and the possibility of East-West commuting. However, we also observe an inversion of this relationship for later periods: That is, along with a second wave of East-West movements around 2001 net flows out of East Germany were much higher than expected after controlling for its weak labour market and macroeconomic performance. Since this second wave is also accompanied by a gradual fading out of economic distortions, this supports the view of repressed migration flows for that period.
Keywords: C33; J61; R23; 330; Internal migration; Panel VAR; System GMM; Binnenwanderung; Regionaler Arbeitsmarkt; Deutschland